Degradation Mechanisms in Organic Lead Halide Perovskite Light‐Emitting Diodes. Issue 22 (2nd September 2019) - Prakasam, Vittal; Tordera, Daniel; Bolink, Henk J.; Gelinck, Gerwin
Abstract: Organic–inorganic metal halide perovskites have attracted significant attention for low‐cost, high‐efficiency, color‐pure light‐emitting applications. However, as seen in many reports so‐far, perovskite light‐emitting diodes (PeLED) suffer from poor operational lifetime, limiting their practical use. The underlying degradation mechanism is a topic of crucial importance. Here, the degradation mechanisms of methylammonium lead bromide based PeLED are investigated. When the PeLED is electrically biased, there is an initial raise in the luminance followed by a rapid reduction in luminance and current density. Microscopic studies reveal the formation of micrometer‐sized spots that are photoluminescent but not electroluminescent. It is demonstrated that this degradation is due to the formation of gaseous compounds that leads to local delamination of the cathode, thereby reducing the electroluminescence. When the degraded cathode is substituted with a fresh cathode, the initial luminance is largely recovered. By further analyzing the buried interface of the cathode, the formation of lead bromide and gaseous methylamine due to the degradation of the perovskite layer are revealed. These insights will help to further improve the lifetime of PeLEDs. As an example, it is shown that substituting methylammonium cations by cesium leads to longer lifetimes. Abstract : Degradation mechanism in methylammonium lead bromide perovskite light emitting diode is systematically studied. The degradation is due to the decomposition of the perovskite layer under electric bias, leading to the formation of gaseous methylamine and hydrogen bromide which locally delaminates the cathode from the device. Stripping and redepositing a new cathode restores the current injection and luminance.